Determination of DPPH Free Radical Scavenging Activity of Polyphenolic Compounds in Terminalia by HPLC - Li1, Xiaofen; Gao1, Yuntao; Pan1, Xiaoxia; Li1, Wenyi; Tan1, Wei (Asian Journal of Chemistry, 2014)
The spectrophotometric method for the evaluation of 1,1-diphenyl-2-picrylhydrazyl (DPPH•) free radical scavenging activity has certain shortcomings such as like interference from color pigments from natural products and lower sensitivity. A specific HPLC method for evaluating the DPPH free radical scavenging activity of natural products was developed. A gradient elution method was employed to obtain better efficiency of separation. The best chromatographic conditions are as follows. The mobile phase was a mixture of methanol and water (50:50, v/v) pumped at a flow rate of 1 mL/min, the DPPH peaks were monitored at 517 nm and the column temperature was 25 ºC. The proposed HPLC method was applied for the estimation of DPPH free radical scavenging activity of polyphenolic compounds such as gallic acid, vanillic acid, caffeic acid, p-coumaric acid and rutin and the extract of Terminalia. The 50 % radical scavenging activity (IC50) determined by the HPLC method correlated well with that of spectrophotometry. The HPLC method can be used as a reliable method of estimate the antioxidant activity for natural products.